Acinetobacter baumannii Genes Required for Bacterial Survival during Bloodstream Infection - Sargurunathan Subashchandrabose; Sara Smith; Valerie DeOrnellas; Sebastien Crepin; Monica Kole; Carina Zahdeh; Harry L. T. Mobley (mSphere, 2016)
ABSTRACT Acinetobacter baumannii is emerging as a leading global multiple-antibiotic-resistant nosocomial pathogen. The identity of genes essential for pathogenesis in a mammalian host remains largely unknown. Using transposon-directed insertion-site sequencing (TraDIS), we identified A. baumannii genes involved in bacterial survival in a leukopenic mouse model of bloodstream infection. Mice were inoculated with a pooled transposon mutant library derived from 109,000 mutants, and TraDIS was used to map transposon insertion sites in the genomes of bacteria in the inoculum and of bacteria recovered from mouse spleens. Unique transposon insertion sites were mapped and used to calculate a fitness factor for every insertion site based on its relative abundance in the inoculum and postinfection libraries. Eighty-nine transposon insertion mutants that were underrepresented after experimental infection in mice compared to their presence in the inocula were delineated as candidates for further evaluation. Genetically defined mutants lacking feoB (ferrous iron import), ddc (d-ala-d-ala-carboxypeptidase), and pntB (pyridine nucleotide transhydrogenase subunit) exhibited a fitness defect during systemic infection resulting from bacteremia. In vitro, these mutants, as well as a fepA (ferric enterobactin receptor) mutant, are defective in survival in human serum and within macrophages and are hypersensitive to killing by antimicrobial peptides compared to the survival of the parental strain under these conditions. Our data demonstrate that FepA is involved in the uptake of exogenous enterobactin in A. baumannii. Genetic complementation rescues the phenotypes of mutants in assays that emulate conditions encountered during infection. In summary, we have determined novel A. baumannii fitness genes involved in the pathogenesis of mammalian infection. IMPORTANCE A. baumannii is a significant cause of bacterial bloodstream infection in humans. Since multiple antibiotic resistance is becoming more common among strains of A. baumannii, there is an urgent need to develop novel tools to treat infections caused by this dangerous pathogen. To develop knowledge-guided treatment approaches for A. baumannii, a thorough understanding of the mechanism by which this pathogen causes bloodstream infection is required. Here, using a mouse model of infection, we report the identification of A. baumannii genes that are critical for the ability of this pathogen to cause bloodstream infections. This study lays the foundation for future research on A. baumannii genes that can be targeted to develop novel therapeutics against this emerging human pathogen.